Strongyloides fuelleborni kellyi in New Guinea: neglected, ignored and unexplored - Richard S Bradbury (Microbiology Australia, 2021)
Strongyloidiasis remains endemic throughout the Island of New Guinea. While many infections are caused by Strongyloides stercoralis, a second human-infecting Strongyloides species, Strongyloides fuelleborni kellyi, is also present. S. f. kellyi infections are most common in infants and young children, and those with high-intensity infections might develop a potentially fatal protein-losing enteropathy, swollen belly syndrome. Surprisingly little work has been performed on S. f. kellyi. Unlike S. stercoralis, S. f. kellyi is passed in faeces as eggs rather than rhabditiform larvae. There is no specific diagnostic test. This review summarises what is currently known about the biology, epidemiology, and clinical impact of S. f. kellyi infections. Features that might be used to differentiate S. f. kellyi from hookworm and S. stercoralis are also discussed. S. f. kellyi remains a neglected, ignored, and unexplored human helminth infection, worthy of further research.